2018
DOI: 10.13057/biodiv/d190430
|View full text |Cite
|
Sign up to set email alerts
|

Carbon mineralization dynamics of tropical peats in relation to peat characteristics

Abstract: Saidy AR, Mariana ZT, Adji FA, Nusantara RW, Fitria I, Syahrinudin. 2018. Carbon mineralization dynamics of tropicalpeats in relation to peat characteristics. Biodiversitas 19: 1413-1421. Understanding the dynamics of carbon mineralization of peats inthe tropical areas is of essential significance in controlling carbon dioxide (CO2) gas emission rates. An incubation study of tropicalpeats sampled from 3 different sites of the Barito Basin on the Borneo Island, Indonesia (uncultivated, used for paddy cultivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…This indicates that the change in carbon mineralization in peat that produces CO2 and CH4 with the addition of coal fly-ash is not related to changes in peat pH. The results of the study are in agreement with previous studies reported that pH of peat does not correlated with carbon mineralization of peatlands [10,21].…”
Section: Influence Of Coal Fly-ash Application On Production Of Co2 and Ch4supporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that the change in carbon mineralization in peat that produces CO2 and CH4 with the addition of coal fly-ash is not related to changes in peat pH. The results of the study are in agreement with previous studies reported that pH of peat does not correlated with carbon mineralization of peatlands [10,21].…”
Section: Influence Of Coal Fly-ash Application On Production Of Co2 and Ch4supporting
confidence: 92%
“…As a result of the rapidly increasing population, part of the tropical peatlands in Indonesia has been reclaimed for agricultural cultivation [9,10]. The use of tropical peatlands as agricultural land has resulted in increased emissions of green house gases (GHG) of reclaimed tropical peatlands.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest carbohydrate content in burned peatland produced the lowest CO2 emission, while high CO2 emission was produced from a high content of carbohydrates on shrubspeatland (Figure 4.A). Several previous studies have also shown that peatlands with low carbohydrate content exhibit low CO2 emission, while high CO2 emission is generally observed in peatlands with high carbohydrate content (Grover and Baldock 2013;Saidy et al 2018).…”
Section: Relationship Between Peat Characteristics and Ch4 And Co2 Em...mentioning
confidence: 82%
“…The decrease in carbohydrates and increase in lignin contents with changes in land use from uncultivated peatlands to cultivated peatlands are in agreement with the concept of changes in the chemical structure of organic C contained in peatlands with agricultural activities. Several agricultural activities in peatlands, such as drainage, fertilizing and liming, enhance the decomposition process of organic C contained in the peats, which in turn causes a decrease in organic C with structures that are easily decomposed, such as carbohydrates and results in the accumulation of organic C that is resistant to biodegradation such as lignin (Saidy et al 2018;Saidy et al 2020).…”
Section: Diversity In Peatland Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation